MULTIMETHOD APPROACH TO THE STUDY OF SUBSURFACE IN MERAK BATIN HOT SPRING, NATAR, LAMPUNG - Santoso, Nono Agus; Junian, Wahyu Eko; Ramayanti, Fitria; Rizki, Reza; Alawiyah, Susanti (Institut Teknologi Sepuluh Nopember, 2025)
Merak Batin Natar hot spring is a geothermal manifestation located far (16 km) from the nearest volcanic edifice and thus is of local scientific interest. The driver of this hot spring has never studied in detail, and whether this system links to the distant volcanic body is an open question. The purpose of this study was to obtain a subsurface model of the Natar hot spring. The method used is a combination of magnetic, geoelectric and geochemical methods. Based on the results of the study, it was found that the subsurface model of the Natar hot spring consists of an unaltered and altered zone. This hot spring belongs to the outflow zone, so it is natural to be in the lowlands and far from the volcano.